The development and empirical validation of the Q-PDN: A questionnaire measuring continuing professional development of nurses. (January 2015) - Brekelmans, Gerard; Maassen, Susanne; Poell, Rob F.; van Wijk, Kees
Summary: Background: Although separate studies among nurses have been conducted into their continuing professional development (CPD) motives, importance attached to CPD, conditions deemed needed for CPD, and actual CPD activities undertaken, these variables have not yet been investigated at the same time, on the same sample. Objectives: The aim of this study is to report on the development and initial psychometric testing of the Q-PDN, a questionnaire measuring several aspects of CPD among nurses. Method: Based on a survey administered to 1329 nurses in hospitals in the Netherlands, a multi-dimensional instrument for CPD was validated. The constructs 'CPD motives', 'CPD importance', 'CPD conditions', and 'CPD activities undertaken' were established through factor analyses. Results: Reliability analyses showed satisfactory to good Cronbach's alpha scores on all factors, ranging from .70 to .89. Conclusion: Using this instrument can stimulate and support CPD of nurses, which has been shown to contribute to increasing the quality of care. Human resource development (HRD) professionals, educators in healthcare, and managers can use this questionnaire to gain insight in the extent to which nurses undertake CPD activities, in the importance they attribute to CPD activities, in the conditions they deem necessary to participate in CPD, and in the motives that they have to engage in CPD.